2016
DOI: 10.1002/ejic.201601098
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Selectivity and Reactivity of Metal‐Substituted Polyoxometalates as Artificial Proteases by Varying the Nature of the Embedded Lewis Acid Metal Ion

Abstract: The hydrolysis of horse heart cytochrome c (cytC) protein by two isostructural Keggin‐type polyoxometalates (POMs), (Me2NH2)10[Ce(α‐PW11O39)2] (Ce1–K2) and (Et2NH2)10[Zr(PW11O39)2] (Zr1–K2), which differ in the nature of the embedded Lewis acid metal ion, has been investigated. In the presence of Ce1–K2, selective hydrolysis of cytC was observed at the Trp60‐Lys61 and Gly78‐Thr79 peptide bonds at pH 7.4 and 37 °C. However, the isostructural Zr1–K2 exhibited a lower reactivity and different selectivity, cleavin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 51 publications
2
65
0
Order By: Relevance
“…Zr(IV)‐substituted polyoxometalates (Zr‐POMs, I P in Figure ) are metal‐oxygen clusters that do not exhibit substrate specificity and hydrolyze multiple peptide bonds of many critical molecules such as human serum albumin (HSA), HEWL, myoglobin, insulin chain B and cytochrome c . Among these substrates, HSA has been considered as an excellent model to study the physicochemical basis of drug–protein interactions due to its biological functions (Figure ) .…”
Section: Peptide and Phosphoester Hydrolysis By Synthetic Analoguesmentioning
confidence: 99%
See 1 more Smart Citation
“…Zr(IV)‐substituted polyoxometalates (Zr‐POMs, I P in Figure ) are metal‐oxygen clusters that do not exhibit substrate specificity and hydrolyze multiple peptide bonds of many critical molecules such as human serum albumin (HSA), HEWL, myoglobin, insulin chain B and cytochrome c . Among these substrates, HSA has been considered as an excellent model to study the physicochemical basis of drug–protein interactions due to its biological functions (Figure ) .…”
Section: Peptide and Phosphoester Hydrolysis By Synthetic Analoguesmentioning
confidence: 99%
“…In this review, activities of two bioinspired synthetic analogues such as polyoxometalates (POMs, I P ), and 1,4,7,10‐tetraazacyclododecane (cyclen, I C ) and their analogues that similar to IDE and GpdQ lack substrate specificity are also discussed (Figure ). Recently, I P complexes have been proposed as novel artificial metalloproteases and nucleases . They are oxo‐anion bridged clusters of metal ions such as Ti(IV), Zr(IV), and Ce(IV) that have been reported to hydrolyze hen egg white lysozyme (HEWL), albumins, myoglobin, DNA, and RNA model substrates .…”
Section: Introductionmentioning
confidence: 99%
“…[27] Ac ommonm odification is the embedding of ac atalytically active metal ion into the POM structure, creating metal-substituted POMs. POMs that contain metal ions with high coordination numbers and strong Lewis acidity,s uch as Ce IV ,Z r IV ,a nd Hf IV ,h ave been shown to activate peptide bonds towards hydrolysis and specifically cleave ar ange of globularp roteins, such as hen egg white lysozyme, [28,29] human serum albumin (HSA), [30][31][32][33] horse heart myoglobin, [34,35] cytochromec (Cyt c), [36] transferrin, [37] ovalbumin, [38] and hemoglobin. [39] Ac ombination of complementary techniques was used to study interactions between POMs and these proteins;t he results strongly suggested that the selectivity of hydrolysis was due to specific interactions between negatively charged POM scaffoldsand positivep atches on the protein surface.…”
Section: Introductionmentioning
confidence: 99%
“…Early literature reported that POMs may have antibacterial and antiviral effects, or they can be useful against tumors, for cancer treatment , . In addition, polyoxometalates have long been studied in a variety of biological applications, from drug design to artificial enzymes , . Narasimhan et al identified polyoxometalate K 6 [P 2 Mo 18 O 62 ] to inhibit DNA‐bound Sox2 activity by spectroscopy (TROSY) experiments and molecular docking.…”
Section: Introductionmentioning
confidence: 99%